2018
DOI: 10.2147/ppa.s181604
|View full text |Cite
|
Sign up to set email alerts
|

Improving safety and efficiency in care: multi-stakeholders’ perceptions associated with a peritoneal dialysis virtual care solution

Abstract: BackgroundAlthough there is a growing body of literature on the outcomes and impacts of remote home management with peritoneal dialysis (PD) patients, less is understood how this virtual care solution impacts the quality and efficiency of the healthcare system care. In this context, a study was undertaken to understand the perceptions of patients and their caregivers, healthcare providers, health system decision makers, and vendors associated with a remote monitoring and tracking solution aimed at enhancing th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
0
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 33 publications
0
0
0
Order By: Relevance
“…Jeffs et al 20 found that health care practitioners believe that the eQConnect software, 23 which monitors peritoneal dialysis treatment and health status in patients with chronic kidney disease, can increase efficiency and safety for their patients, although with certain drawbacks. Through an open-ended survey, Craven et al 19 gathered information on the potential of remote monitoring in patients with epilepsy, multiple sclerosis, and depression.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Jeffs et al 20 found that health care practitioners believe that the eQConnect software, 23 which monitors peritoneal dialysis treatment and health status in patients with chronic kidney disease, can increase efficiency and safety for their patients, although with certain drawbacks. Through an open-ended survey, Craven et al 19 gathered information on the potential of remote monitoring in patients with epilepsy, multiple sclerosis, and depression.…”
Section: Resultsmentioning
confidence: 99%
“… 10,14,15,20,21 Patient studies echo the practitioner perceptions, showing that telemedicine does establish confidence in patients 26–29 and reduce emergency or unnecessary in-person visits. 30 Jeffs et al 20 noted that health care practitioners were able to see the supply usage data of patients with chronic kidney disease and address deficiencies in their self-management, further improving the patient’s ability to self-manage.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations